Low-cost natural wastewater treatment technologies in rural communities using Instream Wetland, Moringa Oleifera, and Aeration Weirs – A comparative study. Issue 1 (1st January 2020) - El Gohary, Rasha
Abstract: Low-cost natural wastewater treatment technologies are very useful in developing communities that lacks investment and technologies. Wetland technologies prove excellent results for wastewater treatment. The objective of this study is to compare and propose a new wastewater technologies using wetland, weirs as an aeration source, finally add Mouringa Oleifera seeds which proven effective in removing: suspended substances, turbidity, chemical oxygen demand (COD), color, and other organic pollutants. To cover the objectives, several studies have been carried out, and can be summarized as follows: two study areas were investigated that used instream wetland as a natural treatment and compare the hydraulic design and efficiency for two case studies both in Egyptian drainage systems. Secondly, studied a field aeration weir that already exists in one of the rural drains and studied its ability to improve water quality after aeration system, finally represent a laboratory analysis using Mouringa Oleifera seeds for drainage water treatment. Removal efficiency for the first wetland study area ranged from 35% to 75% for removal of suspended solids, from 58% to 30% for BOD, 57–44% for COD, and 99% for fecal coliform. While in the second instream wetland is 50% for EC, 83.33 for bicarbonate, 44.2% for TDS, 20% for TSS, 60% for BOD, 85% for COD, 63% for calcium, 88% for potassium, 20% for magnesium, 90% for lead, 99% for total and fecal coliform. The removal efficiency when using M. Oleifera is 85.1% for turbidity, 96.1% for total coliform, 82.8% for total coliform, 60% for arsenic, 85% for cadmium, and 90% for nickel. The efficiency for weir as an aeration source is 77.1% for EC, 98% for TDS, 92.9 for bicarbonate, 95.8% for chloride, and 83.3% for phosphate. The studied technologies offer a cheaper alternative to conventional treatment methods without using any chemical substances for treatment and provide minimum operation and maintenance needs. The instream wetland could be replicated to cover a larger percentage of drains recommend using M. Oleifera beside native plants in wetland especially in sedimentation zone, also study weirs as an aeration source.